Critical analysis of municipal climate change adaptation and mitigation plans - Masiero, Érico; Menegaldo, Vanize; Tavares, Silvia Garcia (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This paper critically analyses climate change adaptation and mitigation plans prepared by 18 cities located in five continents since 2005. The aim is to explore the key adopted strategies in the climate mitigation and adaptation plans of these studied cities to identify the relationship between the application of such measures and urban planning practices. Climate change adaptation and mitigation plans of capital cities or national and continental economic centres were consulted and classified according to their commitment to dealing with climate issues and effectively implementing responses. It was observed that the selected cities have a significant concern about the possible impacts of climate change, although there are still considerable discrepancies between what is proposed in the plans and the effective implementation of mitigation measures, especially in Brazilian cities and other developing nations. Even considering severe problems arising from climate change – such as Urban Heat Islands and high energy consumption increasing greenhouse gas emissions – these cities’ proposals still focus on specific actions, with little investment in infrastructure and a lack of monitoring the proposed actions to properly address climate change.